Symmetry-reversals in chiral active matter. Issue 27 (6th June 2018) - Workamp, Marcel; Ramirez, Gustavo; Daniels, Karen E.; Dijksman, Joshua A.
Abstract : A swarm of active-spinner particles displays a reversal of their swarming direction as their packing density is increased, an effect that can be enhanced by adding geometric friction between the particles. Abstract : We perform experiments on an active granular material composed of individually-driven, spinning disks confined within a circular arena. Small bumps at the outer edges of the disks provide a variable amount of interparticle coupling in the form of geometric friction. The disks each spin counter-clockwise, but undergo a transition in their collective circulation around the center of the arena, from a clockwise orbit to a counter-clockwise orbit, as a function of packing fraction ϕ . We identify that, unlike for vibrated granular gases, the particles' velocity distributions are Gaussian over a large range of ϕ . By fitting the speed distribution to a Maxwell–Boltzmann distribution, we identify a temperature-like parameter which is a universal function of ϕ ; this parameter is also equal to the mean translational energy of the particles. We quantify the collective circulation via its solid-body-like rotation rate, and find that this is a universal function centered around a critical packing fraction. In addition, the ratio of orbital kinetic energy to spin kinetic energy is also a universal function for non-zero geometric friction. These findings highlight the important role of both the type of driving and the interparticle interactions (here, geometric friction) in controlling the collective behavior of active granular systems.